2011
DOI: 10.1099/mic.0.046755-0
|View full text |Cite
|
Sign up to set email alerts
|

C-type natriuretic peptide modulates quorum sensing molecule and toxin production in Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa coordinates its virulence expression and establishment in the host in response to modification of its environment. During the infectious process, bacteria are exposed to and can detect eukaryotic products including hormones. It has been shown that P. aeruginosa is sensitive to natriuretic peptides, a family of eukaryotic hormones, through a cyclic nucleotide-dependent sensor system that modulates its cytotoxicity. We observed that pre-treatment of P. aeruginosa PAO1 with C-type natriuret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 102 publications
1
60
3
Order By: Relevance
“…Our previous study showing that the hormone CNP is able to bind AmiC triggering thus both ami operon transcription and an enhancement of the bacterial virulence16 could not directly fit with our present data showing that AmiE, when over-produced, negatively controls virulence in P. aeruginosa . Next to the direct control of amiE transcription by the AmiC/AmiR sensor/regulator pair, it has been shown that the amiE gene translation is under the Crc/Hfq proteins control49.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our previous study showing that the hormone CNP is able to bind AmiC triggering thus both ami operon transcription and an enhancement of the bacterial virulence16 could not directly fit with our present data showing that AmiE, when over-produced, negatively controls virulence in P. aeruginosa . Next to the direct control of amiE transcription by the AmiC/AmiR sensor/regulator pair, it has been shown that the amiE gene translation is under the Crc/Hfq proteins control49.…”
Section: Discussioncontrasting
confidence: 99%
“…In previous studies, we showed that the opportunistic pathogen P. aeruginosa is able to sense the human C-type natriuretic peptide (CNP), which leads to modifying its biofilm formation1216. This responsiveness of P. aeruginosa to this human hormone is relayed by the specific bacterial sensor protein AmiC, which displays a structural and pharmacological profile identical to the human natriuretic receptor subtype C (hNPR-C)12.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The provirulent effect of CNP on P. aeruginosa was shown to result from the increase in the cAMP concentration [37], which activates the virulence factor regulator Vfr [71] (Fig. 1).…”
Section: Effects Of Peptidic Hormones On Gram-negative Bacteriamentioning
confidence: 99%